The Conception and Application of PFL: a Process Functional Programming Language - Kollar, Jan (Інститут програмних систем НАН України, 2004)
A new process functional programming paradigm and its application in PFL – a process functional programming language is introduced in the paper. This paradigm is based on affecting the state represented by the values of memory cells strictly by evaluating expressions. Process functional conception prevents the use of assignments, which is a good basis for reasoning about the programs and systems by direct PFL program profiling and transformation. This paper is oriented to essential constructs of PFL language and its relation to object and parallel programming paradigm.